1990
DOI: 10.1159/000125571
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Indices of Neurohypophyseal Function in the Aging Fischer Rat

Abstract: In order to resolve conflicting reports in the literature on the effect of aging on the hypothalamo neurohypophyseal system (HNS) in rats, multiple parameters associated with the HNS were evaluated in young (4 months), fully mature (14 months), and old (25 months) Fischer 344 rats under basal and stimulated conditions. The hypothalamic hormones oxytocin and vasopressin were compared in radioimmunoassay of serum, urine, brain and pituitary. Information on body weight, water intake, urine output, serum hematocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
4
15
0
Order By: Relevance
“…This may be an artifact reflecting stress reactions by the old rats to the novel laboratory situation. Others have noted highly variable responses in old rats before significant handling (34). Differences in ad libitum intakes between young and old rats seem to depend on strain and whether intakes are adjusted for body weight.…”
Section: Discussionmentioning
confidence: 95%
“…This may be an artifact reflecting stress reactions by the old rats to the novel laboratory situation. Others have noted highly variable responses in old rats before significant handling (34). Differences in ad libitum intakes between young and old rats seem to depend on strain and whether intakes are adjusted for body weight.…”
Section: Discussionmentioning
confidence: 95%
“…This may indicate that old rats are less able to adjust to the stress of the testing situation than young and middle-aged rats. Others (36) have noted increased variability in the responses of old rats due to increased "handling stress" during testing. The variability in responding by older rats, and presumably the stress involved in testing, can be reduced by extensive preexperimental handling (36).…”
Section: Discussionmentioning
confidence: 99%
“…Others (36) have noted increased variability in the responses of old rats due to increased "handling stress" during testing. The variability in responding by older rats, and presumably the stress involved in testing, can be reduced by extensive preexperimental handling (36). Similarly, we have observed highly variable daily water intakes in old rats compared with young rats upon initial receipt from the supplier, which we attributed to shipping stress or a response to the novel laboratory environment (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an in vitro study showed that oxytocin is able to trigger ACTH release from corticotropes via action at V1 receptors (Schlosser et al 1994). However, so far, the role of oxytocin in HPA system regulation is controversial (Fliers et al 1985, Silverman et al 1990, Neumann et al 1999.…”
Section: Discussionmentioning
confidence: 99%